Multifunctional residential complex as a new type of residential building (Международный научный журнал «Инженер», 2026)
The article reveals aspects of the concept of “sustainable urban planning”, which in the construction industrymeans orientation to the creation of multifunctional buildings and territories, intensive use of land resourcesand compact development, meeting the basic needs of society, creating comfortable living conditions for allpopulation groups, as well as limiting the negative impact on the environment and protection of naturalresources. It is proved that multifunctional residential complex is a new type of residential buildings. As aresult of the performed researches the method of definition of the required public premises included in thecomplex is offered, variants of functional-planning structure of the building are established, which can beused to solve the main problems of formation of volume-planning solution of the multifunctional residentialcomplex, proceeding from the town-planning peculiarities of the construction site.